2022
DOI: 10.1108/ijoem-07-2021-1052
|View full text |Cite
|
Sign up to set email alerts
|

Studying key antecedents of disruptive technology adoption in the digital supply chain: an Indian perspective

Abstract: PurposeThe study examines the key drivers of the adoption of disruptive technologies (DTs) in the digital supply chain (DSC) in developing nations.Design/methodology/approachThe data were collected using well-established measures grounded in the diffusion of innovation (DOI) theory. The hypotheses were tested using the structural equation modeling (SEM) approach using SmartPLS. The authors control for the demographics and apply the required statistical diagnostics for robust findings.FindingsThe compatibility … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 98 publications
1
4
0
Order By: Relevance
“…This could be attributed to Malaysia's major technological trends and drive towards industrialization in various sectors, as noted by Salimon et al 30 India was placed second with a total sample size of 1650. It has also seen several efforts in supporting large‐scale organizations to develop and leverage 4IR‐associated technologies, in accordance with Mitra et al 46 Researchers in this country have also channeled their efforts towards supporting SMEs 47 . Globally, the sample size was 1394.…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…This could be attributed to Malaysia's major technological trends and drive towards industrialization in various sectors, as noted by Salimon et al 30 India was placed second with a total sample size of 1650. It has also seen several efforts in supporting large‐scale organizations to develop and leverage 4IR‐associated technologies, in accordance with Mitra et al 46 Researchers in this country have also channeled their efforts towards supporting SMEs 47 . Globally, the sample size was 1394.…”
Section: Resultssupporting
confidence: 53%
“…From a geographical perspective, India was found to be the leader in terms of where the study was conducted per publication count. A reason for this is the regions support of emerging technology as noted by Mitra et al 46 Unsurprisingly, Malaysia was found to be the leader where the sample size of the applicable study was extracted as the region has seen major technology trends in terms of adoption and the drive towards industrialization in various sectors. This could be attributed to specific efforts to enhance the use of emerging technologies such as dedicated innovation hubs and resource allocation that have been shown to be effective in addressing key technology adoption constructs 30 .…”
Section: Discussionmentioning
confidence: 99%
“…6.2 Using technology to increase resilience in complex supply chains While our paper's findings provide valuable insights into how the complexity of internal and external operations affects supply chain recovery times, additional factors can impact a firm's ability to recover from disruptions. In particular, high technologies such as Machine Learning (ML), Artificial Intelligence (AI) and Internet of Things (IoT) can play a significant role in improving supply chain resilience and recovery (Mitra et al, 2022). ML and AI, for example, can be used to analyze vast amounts of data from various sources to identify patterns and insights that can help firms predict and prepare for potential disruptions (Brintrup et al, 2020).…”
Section: Theoretical and Managerial Implicationsmentioning
confidence: 99%
“…This study has key results that contribute to the literature on the ASC, especially at the intersection of Industry 4.0 and emerging markets (Mitra et al , 2022). Firstly, the UOI is a positive contributor to SCC and mediated VU and SCC's relationship.…”
Section: Discussion Conclusion and Limitationsmentioning
confidence: 84%